Fungal Mechanobiology: High Shear Forces Increase Rhizopus Virulence. (4th October 2017) - Tatara, Alexander; Albert, Nathaniel; Kontoyiannis, Dimitrios P
Abstract: Background: It has been observed in both civilian and military populations that high-energy events, such as tornados and blast injuries, have been associated with mucormycosis in otherwise immunocompetent patients. However, the effects of high shear force directly on fungal biology have not been explored. In order to elucidate the relationship between fungal mechanobiology and virulence, R. oryzae was exposed to high shear stress. Subsequent changes in virulence were measured in a validated fly model of mucormycosis. Finally, spores were simultaneously exposed to high shear forces and calcineurin inhibitors to determine whether this classical stress pathway was involved in changes in virulence in response to shear force. Methods: 10 4 or 10 7 spores/ml of R. oryzae in 100 ml saline were either: (1) grown in static culture (CNTRL); (2) subjected to stirring at 1100 RPMs for 30–45 minutes (Tornadic Physical Shear Challenge, TPSC), or 3) subjected to TPSC in the presence of the calcineurin inhibitor tacrolimus (TPSCS + TAC). Wild-type flies were subsequently infected via dorsal thorax inoculation and monitored for survival over 7 days ( n = 26 per group; performed in triplicate). Results: Flies inoculated with R. oryzae exposed to high shear stress experienced significantly greater mortality compared with spores grown under static conditions ( P < 0.001). Co-culture of spores grown under TPSC with tacrolimus (1 mg/ml) resulted in increased fly survival ( P < 0.001). In fact, there was no significant difference between flies inoculated with spores subjected to high shear and TAC and spores grown under static conditions ( P = 0.934). Conclusion: Fungal exposure to high shear stress increases virulence. As calcineurin inhibition completely mitigated the effect of shear stress on Mucorales virulence, activation of the calcineurin stress response may play an important role in the mechanotransduction of shear stress to increased fungal virulence. Disclosures: D. P. Kontoyiannis, Pfizer: Research Contractor, Research support and Speaker honorarium.Astellas: Research Contractor, Research support and Speaker honorarium. Merck: Honorarium, Speaker honorarium. Cidara: Honorarium, Speaker honorarium. Amplyx: Honorarium, Speaker honorarium. F2G: Honorarium, Speaker honorarium